2007
DOI: 10.4049/jimmunol.178.9.5949
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Priming in Normal Pregnancy and Preeclampsia: The Role of Circulating Syncytiotrophoblast Microparticles

Abstract: Systemic inflammatory responsiveness was studied in normal human pregnancy and its specific inflammatory disorder, pre-eclampsia. Compared with nonpregnancy, monocytes were primed to produce more TNF-α throughout normal pregnancy, more IL-12p70 in the first and second trimesters, and more IL-18 in the first trimester only. Intracellular cytokine measurements (TNF-α and IL12p70) showed little change by comparison. IFN-γ production was suppressed in all three trimesters. In pre-eclampsia, IL-18 secretion was inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
266
1
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 401 publications
(304 citation statements)
references
References 48 publications
14
266
1
15
Order By: Relevance
“…Significantly higher levels in uterine venous blood vs peripheral venous blood in PE (28.7 vs 10.0 ng mL À1 ) and in uterine vs peripheral venous blood NP (9.1 vs 2.3 ng mL À1 ) Germain et al 2007 Blood samples taken from NP at first (n ¼ 10), second (n ¼ 10) and third (n ¼ 14) trimester and at delivery from PE (n ¼ 14). EV: two-step centrifugation ELISA using NDOG2 antibody In NP pregnancy, unbound STBEV plasma levels significantly increase during second and third trimester as determined by protein concentration (mean range 10-30 ng mL À1 vs first trimester 5 ng mL À1 ).…”
Section: Sources Of Stbevs and Isolation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly higher levels in uterine venous blood vs peripheral venous blood in PE (28.7 vs 10.0 ng mL À1 ) and in uterine vs peripheral venous blood NP (9.1 vs 2.3 ng mL À1 ) Germain et al 2007 Blood samples taken from NP at first (n ¼ 10), second (n ¼ 10) and third (n ¼ 14) trimester and at delivery from PE (n ¼ 14). EV: two-step centrifugation ELISA using NDOG2 antibody In NP pregnancy, unbound STBEV plasma levels significantly increase during second and third trimester as determined by protein concentration (mean range 10-30 ng mL À1 vs first trimester 5 ng mL À1 ).…”
Section: Sources Of Stbevs and Isolation Methodsmentioning
confidence: 99%
“…We (Messerli et al 2010) and others (Germain et al 2007) have shown that STBEVs can activate peripheral blood monocytes, inducing the release of various inflammatory cytokines, which has led to the suggestion that the higher levels of STBEVs may contribute to the systemic inflammatory response seen in PE (Redman et al 2012). In addition, several groups have shown, using in vitro models, that STBEVs can reduce proliferation and damage the integrity of cultured endothelial cell monolayers (Redman and Sargent 2009;Roberts and Escudero 2012).…”
Section: Functionmentioning
confidence: 98%
“…The preeclamptic placenta is hypoxic and experiences oxidative stress. It is postulated that the observed increased expression in preeclamptic patients of these circulating microparticles is a consequence of inflammatory and oxidative stress [9]. In an apparent 'positive feedback loop', STBM are capable of stimulating pro-inflammatory cytokine release when cultured in vitro with peripheral blood mononuclear cells [9].…”
Section: Pro-and Anti-coagulant Clotting Pathwaysmentioning
confidence: 99%
“…It is postulated that the observed increased expression in preeclamptic patients of these circulating microparticles is a consequence of inflammatory and oxidative stress [9]. In an apparent 'positive feedback loop', STBM are capable of stimulating pro-inflammatory cytokine release when cultured in vitro with peripheral blood mononuclear cells [9]. Furthermore, STBMs collected by perfusion of the maternal side of placentae (taken at the time of caesarean section) from healthy pregnant women and women with preeclampsia have been shown to have TF activity in a calibrated automated thrombography assay, in which thrombin generation is determined by cleavage of a fluorogenic thrombin substrate [61].…”
Section: Pro-and Anti-coagulant Clotting Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation